Editorial: Sustainable production of renewable energy from non‐food crops. Issue 4 (April 2015) - Laimer, Margit; Maghuly, Fatemeh; Vollmann, Johann; Carels, Nicolas
<x xml:space="preserve">Abstract</x> Since the world faced the petroleum crisis in the 1970s and people started to realize the limitation of fossil energy resources coupled with concerns over the effects of increasing carbon dioxide in the atmosphere, major efforts were devoted to the search for alternative energy sources. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>